التصميم الانشائي لمركز البحوث الزراعية - البطران, رهف; فنون, أحمد; ابو زلطة, رامي; حسنية, ربيع (جامعة بوليتكنك فلسطين - مباني, 2021)
Structural design is important and results in all outputs related to the stability of all structural elements, where the structural safety of these elements is evaluated after carrying out the process of determining the loads, analysis and structural design. The selection of sections is done depending on the provision of the structural safety .factor as well as on the economic cost The building consists of three floors, and the total area is about (5000) square meters, and the design is distinguished from the architectural point of view that it was done in a manner based on the multiplicity of space blocks and distributed in a coherent manner in terms of aesthetics and functionality, in addition to that attention was paid .when distributing the blocks to provide comfort, ease and speed Access to users The ground floor has a floor area of about 2270 square meters, consisting of rooms for education, offices and a number of laboratories, a cafeteria, a kitchen and a multi-use hall. The first floor has a floor area of about 2,200 square meters, consisting of research offices, a biotechnology department, a seed bank, a equipment department, an animal health laboratory, a space for tools, a plant drying area, rooms for personal affairs and an accounting room. The second floor is about 360 square meters, and it .consists of bedrooms, a dining hall, and bathrooms The importance of the project lies in the diversity of the structural elements in the building such as bridges, columns and concrete slabs, and the multiplicity of blocks and the presence of retreats in the floor areas It is worth noting that the Jordanian code will be used to determine live loads, and to determine earthquake loads, as for structural analysis and section design, the American code (ACI_318_08) will be used, and it must be noted that some computer - :programs such as .ETABS, ATIR, SP Column, Microsoft office and AutoCAD In the stage of the graduation project, a detailed construction study will be presented in terms of analysis, design and detailed plans for what has been designed التصميم اإلنشائي مهم وينتج عنه جميع المخرجات المتعلقة بثبات جميع العناصر اإلنشائية , حيث يتم تقييم األمان اإلنشائي لهذه العناصر بعد القيام بعملية تحديد األحمال والتحليل والتصميم اإلنشائي .اختيار المقاطع يتم اعتمادا على توفير عامل األمان اإلنشائي وكذلك اعتمادا على التكلفة االقتصادية . يتكون المبنى من ثالث طوابق , وتبلغ المساحة اإلجمالية حوالي )5000( متر مربع , ويتميز التصميم من الناحية المعمارية للمشروع بأنه تم بأسلوب يقوم على تعدد الكتل الفراغية وتوزيعها بشكل متناسق من الناحية الجمالية والوظيفية , إضافة إلى أنه تم االهتمام عند توزيع الكتل بتوفير الراحة والسهولة وسرعة الوصول للمستخدمين . الطابق األرضي مساحته الطابقية حوالي 2270 متربع مربع عبارة عن غرف للتعليم ومكاتب وعدد من المختبرات, كافتيريا ومطبخ وقاعه متعددة االستخدامات. والطابق األول مساحته الطابقية حوالي 2200 متر مربع , يتكون من مكاتب للبحث وقسم للتكنولوجيا الحيوية وبنك للبذور وقسم للمعدات ومختبر لصحة الحيوانات ومساحة لألدوات ومنطقة لتجفيف النباتات وغرف للشؤون الشخصية وغرفة محاسبة. أما الطابق الثاني مساحته حوالي 360 متر مربع , يتكون من غرف نوم وقاعة للطعام وحمامات. تكمن أهمية المشروع في تنوع العناصر اإلنشائية في المبنى مثل الجسور واألعمدة والبالطات الخرسانية , وتعدد الكتل ووجود تراجعات في المساحات الطابقية من الجدير بالذكر أنه سيتم استخدام الكود األردني لتحديد األحمال الحية , ولتحديد أحمال الزالزل , أما بالنسبة للتحليل اإلنشائي وتصميم المقاطع فسيتم استخدام الكود األمريكي)ACI_318_08( , وال بد من اإلشارة إلى أنه سيتم االعتماد على بعض برامج الحاسوب مثل :- ETABS,ATIR, SP Column, Microsoft office and AutoCAD . وفي مرحلة مشروع التخرج سيتم تقديم دراسة إنشائية تفصيلية من حيث التحليل والتصميم وتقديم مخططات تفصيلية لما تم تصميمه
no of pages 85 , CD , مباني 11/2021
Keywords: التصاميم الانشائية; المباني الزراعية